Fighting multidrug-resistant Enterococcus faecalis via interfering with virulence factors using green synthesized nanoparticles. (December 2022) - Yousef, Abdullah; Abu-Elghait, Mohammed; Barghoth, Mohammed G.; Elazzazy, Ahmed M.; Desouky, Said E.
Abstract: This study aims to synthesize silver nanoparticles by the green method and test it against specific virulence factors in multi-drug resistant Enterococcus faecalis bacteria. virulence factors of E. faecalis clinical isolates were determined and the most potent isolate was selected for further investigations. The prepared Ag-NPs were characterized using UV spectroscopy, FTIR spectroscopy, dynamic light scattering, and transmission electron microscopy (TEM). The result revealed the concentration of 0.0625 mg/ml Ag-NPs was significantly reducing virulence factors in multidrug-resistant E. faecalis without affecting planktonic cell growth. UV–Visible spectroscopy characterization revealed a characteristic surface Plasmon band [SPR] at a wavelength ranging from 256 to 345 and 510 nm in the prepared Ag-NPs. dynamic light scattering indicated it tended to an electrostatic attraction between nanoparticles in the prepared solution. TEM images revealed the average size of Ag-NPs were prepared to be 28.8 nm and the shape was spherical. Green synthesized Ag-NPs have the ability to combat multi-drug-resistant E. faecalis via reducing virulence factors, which is considered a good approach toward resolving the multidrug resistance crisis. Graphical abstract: Image 1 Highlights: Our study explores an innovative therapeutic strategy for fighting bacterial antibiotic resistance phenomena. Ag-NPs produced by Moringa olifera tested against virulence factors in MDR  Enterococcus faecalis . Gelatinase activity, biofilm formation, Casinase and hemolytic activity were affected by green synthesized Ag-NPs. Ag-NPs inhibit virulence factors at 0.0625 mg/ml without affecting planktonic cell growth. The drug combination between vancomycin and Ag-NPs exhibits a synergistic effect against multi drug resistant E. faecalis.